Study of anthropometric measurement of distal femur among Malay, Chinese and Indian - Wei, Chew Yu (2021)
Introduction: Knee joint replacement surgery requires a good shape match between the implants and the resected knee surface to ensure good outcome. It is well known that Asian knees are smaller compared to their Western counterparts. However, there is paucity of data regarding the anthropometric measurement of distal femur within the Asian population. Hence, our main objective is to study the difference between the anthropometric measurement of distal femur within the Asian population particularly the Malay, Chinese and Indian. Methodology: A total of 90 CT knee images of Malay, Chinese and Indian subjects performed were measured using axial slice perpendicular to the long axis of femur. Parameters measured are anteroposterior measurement of lateral (APL) and medial (APM) femoral condyle and mediolateral (ML) measurement of distal femur condyle. Aspect ratio were calculated using the formula (ML/AP). All parameters were measured up to 0.1mm and statistical analysis was performed using IBM SPSS Statistics Version 24. Two-way Analysis of Variance (ANOVA) was conducted to analyze the influence of two independent variables (gender and race) on anthropometric measurement of distal femur. Any differences in anthropometric measure of distal femur between races were ascertained using one-way Analysis of Covariance (ANCOVA) after controlling the age. Pearson correlation test was used to measure correlation between distal femur morphology and age. Results: There was a significant difference of AP Medial measurement of distal femur between three races (F (2,89): 6.88, p = 0.002). Difference in gender also showed a significant effect on the AP medial (F (1,86): 33.36, p < 0.001) and AP lateral (F (1,86): 26.79, p < 0.001) measurement of distal femur. Our study showed strong correlation between AP and ML measurement indicating that with increasing AP length, the ML width increases. Indian population noted to have the most pronounced knee-implant mismatch in our study. Conclusion: We concluded that not all Asian knees are the same and thus similar implant designs cannot be universally applied throughout all Asian population.